1998
DOI: 10.1016/s0042-6989(97)00230-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of estimating time to collision using binocular and monocular information

Abstract: We measured both the just-noticeable difference in time to collision (TTC) with an approaching object, and the absolute accuracy in estimating TTC in the following cases: only binocular information available; only monocular information available; both binocular and monocular information available as in the everyday situation. Observers could discriminate trial-to-trial variations in TTC on the basis of binocular information alone: the just-noticeable difference in TTC (5.1-9.8%) was the same for a small (0.03 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
192
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(207 citation statements)
references
References 33 publications
13
192
1
1
Order By: Relevance
“…Thus, as expected, both the accurate cue (TTC v ) and heuristic cues such as the final optical size were significantly associated with the TTC estimates. This finding is compatible with data from DeLucia et al (2016), obtained in both an audio-visual and a visual-only condition, whereas Gray and Regan (1998) reported that the final optical size, final rate of optical expansion and the change in visual angle across the presentation duration showed no relation to TTC estimates in a visual-only condition. As expected, the TTC estimates increased with the actual visual TTC, with the final visual distance (Law et al, 1993), and with the inverse of the final optical size (DeLucia, 1991).…”
Section: Visual-only Conditionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, as expected, both the accurate cue (TTC v ) and heuristic cues such as the final optical size were significantly associated with the TTC estimates. This finding is compatible with data from DeLucia et al (2016), obtained in both an audio-visual and a visual-only condition, whereas Gray and Regan (1998) reported that the final optical size, final rate of optical expansion and the change in visual angle across the presentation duration showed no relation to TTC estimates in a visual-only condition. As expected, the TTC estimates increased with the actual visual TTC, with the final visual distance (Law et al, 1993), and with the inverse of the final optical size (DeLucia, 1991).…”
Section: Visual-only Conditionsupporting
confidence: 90%
“…Vehicle size and presentation duration were varied in order to reduce the correlations between such cues as final optical size and final rate of expansion (cf. Gray & Regan, 1998;Oberfeld, Hecht, & Landwehr, 2011), so that the observer's weightings of these cues could be more easily estimated in the analyses. Consequently, the starting distance of the vehicle varied across trials on the basis of presentation duration, vehicle speed, and TTC level (see the Study Design section for details).…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that multiple sources of monocular and binocular information may contribute to the timing of a catch. Similar results were obtained by Gray and Regan (1998), who showed in several psychophysical experiments that more accurate ttc judgements were made when both monocular and binocular information was available. Second, Rushton and Wann (1999) applied virtual reality to create a similar misjudgement: participants had to catch virtual balls of which the diameter was computationally scaled, so that the ball appeared to arrive 100 ms earlier or later than specified by retinal disparity.…”
Section: Introductionsupporting
confidence: 86%